Hybrid p-type ZnO film and n-type ZnO nanorod p-n homo-junction for efficient photovoltaic applications - Lee, J; Lee, J; Lee, S; Nam, H; Hong, J; Cha, S; Park, Y; Kim, J (2010)
Simple hybrid p-n homo-junctions using p-type ZnO thin films and n-type nanorods grown on fluorine tin oxide (FTO) substrates for photovoltaic applications are described. The ZnO nanorods (1.5 μm) were synthesized via an aqueous solution method with zinc nitrate hexahydrate and hexamethylenetetramine on ZnO seed layers. The 10-nm-thick ZnO seed layers showed n-type conductivity on FTO substrates and were deposited with a sputtering-based method. After synthesizing ZnO nanorods, aluminum-nitride co-doped p-type ZnO films (200 nm) were efficiently grown using pre-activated nitrogen (N) plasma sources with an inductively-coupled dual-target co-sputtering system. The structural and electrical properties of hybrid p-n homo-junctions were investigated by scanning electron microscopy, transmittance spectrophotometry, and I-V measurements. © 2010 Elsevier B.V. All rights reserved.